2023
DOI: 10.1021/acsnano.3c06133
|View full text |Cite
|
Sign up to set email alerts
|

Spin Polarization in Transport Studies of Chirality-Induced Spin Selectivity

Tianhan Liu,
Paul S. Weiss

Abstract: Chirality-induced spin selectivity (CISS) is a recently discovered effect in which structural chirality can result in different conductivities for electrons with opposite spins. In the CISS community, the degree of spin polarization is commonly used to describe the efficiency of the spin filtering/polarizing process, as it represents the fraction of spins aligned along the chiral axis of chiral materials originating from non-spin-polarized currents. However, the methods of defining, calculating, and analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Using this model, it can be shown that, normalM normalR = I false↑ I false↓ I false↑ + I false↓ = P F M P C h i r a l where I ↑ ↓ is the measured current with magnetization direction indicated by the subscript and P Chiral is the spin polarization of the chiral system. This clearly shows that the total MR can never exceed the polarization of the ferromagnet, even when we assume a perfect spin polarization of the chiral system ( P Chiral = 1), as was recently also pointed out by Liu and Weiss and others. Note that here the MR definition commonly used for CISS is applied, which is different from the conventional definition of the TMR ratio applied in the Julière model.…”
Section: Problems With the Spin Transport Interpretation Of Two Termi...supporting
confidence: 76%
See 2 more Smart Citations
“…Using this model, it can be shown that, normalM normalR = I false↑ I false↓ I false↑ + I false↓ = P F M P C h i r a l where I ↑ ↓ is the measured current with magnetization direction indicated by the subscript and P Chiral is the spin polarization of the chiral system. This clearly shows that the total MR can never exceed the polarization of the ferromagnet, even when we assume a perfect spin polarization of the chiral system ( P Chiral = 1), as was recently also pointed out by Liu and Weiss and others. Note that here the MR definition commonly used for CISS is applied, which is different from the conventional definition of the TMR ratio applied in the Julière model.…”
Section: Problems With the Spin Transport Interpretation Of Two Termi...supporting
confidence: 76%
“…However, the measured MR is often directly interpreted in terms of the spin polarization of the transmitted electrons. It is crucial to distinguish the MR ,, generated by the entire circuit (chiral system + ferromagnet) from mechanisms that generate the spin-dependent electron transport in the chiral systems themselves. , In this work, we assume the presence of directional spin-dependent transmission and reflection in the chiral systems itself. However, despite this assumption, below, we identify five main problems with the common interpretation of the measured MR in terms of spin-dependent transport.…”
Section: Problems With the Spin Transport Interpretation Of Two Termi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this treatment contrasts with classical definitions in which the spin polarization is formally given as the difference in populations for spin up and spin down electrons. 16,17 Thus, care must be taken when comparing findings between different measurement techniques.…”
Section: Methods For Measuring Cissmentioning
confidence: 99%
“…For example, the CISS literature often defines polarizations as normalized anisotropies in electron currents or charge transfer rate constants, and these quantities can be convoluted with the spin density of states. However, this treatment contrasts with classical definitions in which the spin polarization is formally given as the difference in populations for spin up and spin down electrons. , Thus, care must be taken when comparing findings between different measurement techniques.…”
Section: Methods For Measuring Cissmentioning
confidence: 99%